Reading and (not) seeing? - (:unkn) unknown (My University, 2016)
A Veil of Footsteps. Memoir of a Nomadic Fictional Character, by South African-born writer and painter Breyten Breytenbach, is composed of short texts ranging in length from one to around ten pages. The work, published in 2008, may be read as the travel notes of a nomadic writer and painter. Cyclical journeys to Paris, Spain, Gorée Island off the coast of Senegal, South Africa and New York are described. The texts correspond to an outer reality, or truth, as ever since Breytenbach was released from apartheid’s prisons in 1982, he has indeed led a nomadic life, living and working in one place for no longer than a few months, before moving on. Yet the reader becomes aware very early on that the places described in what he calls his “black book of impressions” (AVF 31) correspond to an outer and an inner reality. In places the biographical is fictionalized, and the name the I-narrator gives himself, Breyten Wordfool, is emblematic of this in-between state. In the short text this analysis focuses on, “Paris,” the nomad’s narrative is suspended, and troubled, by the ambiguous evocation of a work of art. The work of art in question is a hand-coloured etching the I-narrator takes to be framed. This paper considers the contradictory manner in which a visually powerful text avoids describing a work of art that is nevertheless placed at its centre. I shall examine the manner in which the narrative runs circles around the etching, which remains a veritable blind spot in the text. This frustrating game of hide and seek will lead the ideal reader to turn to the extra-text, the existing etching, in order to try to determine “what this picture wants,” to borrow W.J.T. Mitchell’s expression. I shall consider the possible significance of the etching technique, which relies on the use of an etching needle (a reminder of the writer’s pen) and then attempt to read the image, before re-considering the meaning of the text alongside the unveiled image.
Keywords: African Research